Plasma parathyroid hormone and cardiovascular disease in treatment‐naive patients with primary hyperparathyroidism: The EPATH trial. Issue 11 (20th August 2017) - Wetzel, Julia; Pilz, Stefan; Grübler, Martin R.; Fahrleitner‐Pammer, Astrid; Dimai, Hans P.; von Lewinski, Dirk; Kolesnik, Ewald; Perl, Sabine; Trummer, Christian; Schwetz, Verena; Meinitzer, Andreas; Belyavskiy, Evgeny; et al.
Abstract : Patients with primary hyperparathyroidism are at increased risk for high blood pressure, vascular stiffening, and left ventricular hypertrophy, but previous studies have failed to demonstrate the direct associations with circulating parathyroid hormone (PTH) levels. The authors investigated cross‐sectional relationships between PTH and 24‐hour pulse wave velocity, nocturnal systolic blood pressure, and left ventricular mass index in patients with primary hyperparathyroidism who were treatment‐naive with cinacalcet, renin‐angiotensin‐aldosterone‐system inhibitors, and thiazide or loop diuretics. In 76 patients, mean±SD of pulse wave velocity, nocturnal systolic blood pressure, and left ventricular mass index values were 9.3±1.8 m/s, 116.6±17.0 mm Hg, and 92.8±23.0 g/m². In multivariate linear regression analyses with adjustment for potentially confounding parameters, PTH was independently associated with nocturnal systolic blood pressure (adjusted ß coefficient=.284, P =.040), mean 24‐hour pulse wave velocity (ß=.199, P =.001), and left ventricular mass index (ß=.252, P =.025). PTH may promote vascular and cardiac remodeling in primary hyperparathyroidism. Interventional trials are needed to test the antihypertensive and cardioprotective effects of PTH‐inhibitory treatment strategies.